Integrated Quality Management toward Community Economic Empowerment at Micro Waqf Bank - Nur Alfy Syahriana; Mohammad Fauzan Ni’ami; Sudirman - (Jurnal Ilmiah Ekonomi Islam, 2023)
Abstract The issue of poverty that occurred for years brings the government's attention until it appears breakthroughs. One of the breakthroughs in the economic sector is to establish Micro Waqf Bank (BWM) which is expected to improve community economic development surrounding the Islamic Boarding School. This research aims to describe Integrated Quality Management (IQM) theory toward the BWM management process, to explain the management of Micro Waqf Bank (BWM) Tebuireng in detail, and to show how the implementation of IQM in Micro Waqf Bank (BWM) Tebuireng. This research involved an empirical study with a qualitative approach. While the primary and secondary data sources were collected through interviews and documentation. The research results indicated that the concept of IQM can be used as a benchmark for whether the quality management of financial institutions has been linked to Islamic values or vice versa. The fund management of BWM Tebuireng is divided into three stages, such as fundraising, fund distribution to customers, and regular reports. Finally, the management has been based on the six principles of IQM which include a focus on customers, process improvement, total involvement, avoiding speculation (gharar), avoiding ambiguity, and no coercion. Abstrak Persoalan kemiskinan yang berlangsung selama bertahun-tahun selalu menjadi perhatian pemerintah sampai akhirnya dicetuskan terobosan-terobosan baru. Salah satu bentuk terobosan tersebut dilakukan pada sektor ekonomi melalui pendirian Bank Wakaf Mikro (BWM) yang diharapkan mampu meningkatkan perekonomian masyarakat di sekitar pesantren. Penelitian ini bertujuan untuk memaparkan tawaran teori Integrated Quality Management (IQM) untuk proses pengelolaan BWM. Kemudian menjelaskan pengelolaan BWM Tebuireng secara rinci. Diakhir, akan ditunjukkan bagaimana implementasi IQM di BWM Tebuireng. Penelitian ini termasuk kajian penelitian empiris dengan pendekatan kualitatif. Lalu sumber data primer dan sekunder dikumpulkan melalui serangkaian proses wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa konsep IQM dapat digunakan sebagai tolok ukur apakah pengelolaan lembaga keuangan sudah mempunyai kualitas mutu yang sesuai dengan nilai-nilai ke-Islaman atau justru sebaliknya. Kemudian pengelolaan dana BWM Tebuireng dibagi menjadi tiga tahap, yaitu penghimpunan dana, penyaluran dana kepada nasabah, dan laporan rutin. Terakhir, pengelolaan tersebut sudah sesuai dengan enam prinsip IQM yang meliputi fokus kepada pelanggan (focus on customer), perbaikan proses (process improvement), keterlibatan total (total involvement), terhindar dari spekulasi (gharar), terhindar dari ketidakjelasan, dan tidak adanya paksaan.